2017
DOI: 10.1186/s12870-017-1207-z
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous trehalose improves growth under limiting nitrogen through upregulation of nitrogen metabolism

Abstract: BackgroundThe trehalose (Tre) pathway has strong effects on growth and development in plants through regulation of carbon metabolism. Altering either Tre or trehalose 6-phosphate (T6P) can improve growth and productivity of plants as observed under different water availability. As yet, there are no reports of the effects of modification of Tre orT6P on plant performance under limiting nutrition.ResultsHere we report that nitrogen (N) metabolism is positively affected by exogenous application of Tre in nitrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 34 publications
1
30
1
Order By: Relevance
“…It is known that NH 4 + accumulation in roots needs to be assimilated by the GS/GOGAT cycle [ 57 , 58 ]. Lin et al [ 12 ] showed that by spraying tobacco leaves with trehalose, N assimilation was induced together with GS and GOGAT activities under N-deficient growing conditions. In our experimental system, GS1 was strongly induced by Suc, and to a lesser extent by Gluc, while GOGAT seems to be induced by Gluc addition and repressed by Suc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that NH 4 + accumulation in roots needs to be assimilated by the GS/GOGAT cycle [ 57 , 58 ]. Lin et al [ 12 ] showed that by spraying tobacco leaves with trehalose, N assimilation was induced together with GS and GOGAT activities under N-deficient growing conditions. In our experimental system, GS1 was strongly induced by Suc, and to a lesser extent by Gluc, while GOGAT seems to be induced by Gluc addition and repressed by Suc.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, incremented lateral root (LR) development has been observed in Arabidopsis mutants with defects in the leaf cuticle, which took up more sucrose (Suc) from the medium under high NO 3 − conditions [ 11 ]. Furthermore, exogenous spraying application of trehalose promotes Nicotiana tabacum plant growth under N-limiting conditions by up-regulating N assimilation enzyme activities [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in tobacco, at low concentration (e.g. 8 mM), exogenous Tre can recover the nitrate reductase activity partially, and chlorophyll and total nitrogen content of leaves and rates of photosynthesis were increased through a long-term effect, which can be observed 1–2 weeks after the treatments [23]. In stark contrast, we did not find the expression level of any nitrate reductase genes were changed in our RNA-seq data (S7 and S8 Data).…”
Section: Discussionmentioning
confidence: 99%
“…A couple of studies have been done to investigate gene expression patterns in response to Tre treatment in Arabidopsis seedling cultured in liquid medium by DNA microarray[21, 22]. In tobacco, interestingly, exogenous Tre can effectively increase nitrogen metabolism, and promote tobacco growth under deficient nitrogen that restrict plant growth severely[23].…”
Section: Introductionmentioning
confidence: 99%
“…TRE also acts as a potential signaling metabolite for mediating interactions of plants with pathogenic or symbiotic microorganisms and herbivorous insects. In plants, TRE is involved in tolerance to abiotic stresses, such as high salinity [36], HT [37], nitrogen deficiency [38], and drought [39,40], and biotic stresses such as microorganisms [41] (reviewed in Fernandez et al, 2010 [33]).…”
Section: Introductionmentioning
confidence: 99%